TOXICITY OF AVERMECTIN B1b TO EARTHWORM AND COCKROACHES - S. Siddique; Q. Syed; Y. Saleem; A. Adnan; F. A. Qureshi (Journal of Animal and Plant Sciences, 2015)
The main objective of the present study was to investigate the effect of avermectin B1b on nematodes and arthropods. Avermectin B1b, a component of commercially available abamectin, was obtained as fermentation product of S. avermitilis 41445 and used after purification. In the case of earthworm, a representative nematode, the LC50 values determined for contact filter paper test from Probit’s analysis after 48 and 72 h were 500µg/cm2 and 300µg/cm2 respectively. The mortality increased as the concentration of the applied substance increased. The LC50 values calculated after 7, 14 and 28 days from Probit’s analysis were 712.5248 mg/Kg, 382.6 mg/Kg and 74.6 mg/Kg respectively showing a clear concentration-mortality relationship. For cockroach, a representative arthropod, the LC50 values for mortality were lower for oral exposure as compared to the dermal. The no observed effective concentration (NOEC) and lowest observed effective concentration (LOEC) values determined for earthworm mortality calculated on the basis of student’s t-test were 0.1 mg/Kg and 1.0 mg/Kg respectively. At lower concentrations the cocoon formation was observed with subsequent elimination at 1000 mg /kg of avermectin B1b.  The results of present study revealed that avermectin B1b is highly effective against nematodes and arthropods.
Keywords: Earthworms; cockroaches; avermectin B1b; Probit’s analysis; NOEC; LOEC; LC50 determination